Red and processed meat intake and risk of colorectal adenomas: a systematic review and meta-analysis of epidemiological studies - Aune, Dagfinn; Chan, Doris S. M.; Vieira, Ana Rita; Rosenblatt, Deborah A. Navarro; Vieira, Rui; Greenwood, Darren C.; Kampman, Ellen; Norat, Teresa (Cancer causes & control, 2013)
Background: Current evidence indicates that red and processed meat intake increases the risk of colorectal cancer; however, the association with colorectal adenomas is unclear. Objective: To conduct a systematic review and meta-analysis of epidemiological studies of red and processed meat intake and risk of colorectal adenomas as part of the Continuous Update Project of the World Cancer Research Fund. Design: PubMed and several other databases were searched for relevant studies from their inception up to 31 December 2011. Summary relative risks (RRs) were estimated using a random effects model. Results: Nineteen case–control studies and seven prospective studies were included in the analyses. The summary RR per 100 g/day of red meat was 1.27 (95 % CI 1.16–1.40, I² = 5 %, n = 16) for all studies combined, 1.20 (95 % CI 1.06–1.36, I² = 0 %, n = 6) for prospective studies, and 1.34 (95 % CI 1.12–1.59, I² = 31 %, n = 10) for case–control studies. The summary RR per 50 g/day of processed meat intake was 1.29 (95 % CI 1.10–1.53, I² = 27 %, n = 10) for all studies combined, 1.45 (95 % CI 1.10–1.90, I² = 0 %, n = 2) for prospective studies, and 1.23 (95 % CI 0.99–1.52, I² = 37 %, n = 8) for case–control studies. There was evidence of a nonlinear association between red meat (pnonlinearity < 0.001) and processed meat (pnonlinearity = 0.01) intake and colorectal adenoma risk. Conclusion: These results indicate an elevated risk of colorectal adenomas with intake of red and processed meat, but further prospective studies are warranted.